A longitudinal and co-educational study applied to educational contexts: Correlation between legislation and gender stereotypes - Sánchez Reig, Dámaris; Turpin Gil, Aarón (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The present research paper aims to conduct a longitudinal quasi-experimental study, taking as a sample the students of 3rd and 4th Grade of Primary Education Teacher of the year 2016 and 2022, all with the aim of analyzing their vision of the inclusion of women scientists. From this comparison, a correlation is established that interconnects with the progression of the current legislative framework during two periods, giving as results the clear importance of legislative evolution for the promotion of a more inclusive vision towards women in relation to their ability to access STEM areas.